Structural, lexical, and pragmatic features of american immigration acts in historical perspective - Khoma, Nataliia (Видавництво Львівської політехніки, 2013)
The article deals with the issue of American immigration act as the linguistic phenomena. The main purpose of the study is to fully analyse structure, lexis and pragmatics of American immigration acts. During the analysis the genre of immigration act was defined. Typology of terms and speech acts was suggested alongside with the dynamics in structure, lexis and pragmatics of immigration acts demonstration.
Keywords: immigration act; structural features; lexical and pragmatic features; speech genre; dynamics; term system; lexis